PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERINTEGRASI CHEMO-ENTREPRENEURSHIP DAN HUBUNGANNYA DENGAN LIFE SKILL SISWA DALAM PEMBELAJARAN KIMIA (Universitas Negeri Semarang, 2021)
This study aims to see how student life skills, especially in vocational skills, after using the integrated CEP PjBL learning model. This study uses an associative method with a quantitative approach. Taking population and samples using total random sampling with the population is also the sample used in the study. Collecting data using instruments including, the CEP integrated project-based LKPD which is used as a practical guide as well as a reference in practicum supervision, the model implementation observation sheet to see the implementation of learning carried out to teach students, the life skills observation sheet used in direct life skills assessment when Available learning, as well as the responsibility of the student questionnaire used to measure students' life skills in learning using the CEP integrated PjBL model. The results showed that learning using the CEP integrated PjBL model was proven to be able to help students develop life skills in the aspect of vocational skills so that students had entrepreneurship. This can be seen from the proportion of students' vocational proficiency, namely 74.89%, where the competitiveness of students in sales and the work ethic possessed by students can be categorized as very good, namely 80.27% and 82.45%. The generic life skills of the students were classified as good with the proportion of 77.18% and the specific life skills of the students were classified as good with the proportion of 73.94%.